Application of driven plasma cathode in RF electron gun - Khodak, I.V.; Kushnir, V.A. (Вопросы атомной науки и техники, 2004)
The results of the experimental research of generation of pulsed electron beam in S-band RF gun with driven
plasma cathode are described. There has been designed experimental sample of the cathode based on ferroelectric
ceramics. It has been obtained at RF gun output electron beam with particle energy ≅500 keV, pulsed peak current
of 3 A and pulse duration of 50 ns. Oписано результати експериментального дослідження генерації імпульсного електронного пучка у ВЧ-
гарматі S-діапазону з керованим плазмовим катодом. Було розроблено дослідний зразок катода на основі ферроелектричної кераміки. На виході НВЧ-гармати було отримано електронний пучок з енергією часток ≅
500 кеВ, імпульсним струмом 3 А і тривалістю імпульсу 50 нс. Oписаны результаты экспериментального исследования генерации импульсного электронного пучка в
ВЧ-пушке S-диапазона с управляемым плазменным катодом. Был разработан опытный образец катода на
основе ферроэлектрической керамики. На выходе ВЧ-пушки был получен электронный пучок с энергией частиц ≅500 кэВ, импульсным током 3 А и длительностью импульса 50 нс.